Heartshot - Havill, Steven (Havill, Steven. Posadas County series., 2000)
Posadas County, New Mexico, hugging the San Cristobalmountains separating it from Mexico, has very few mean streets. No city-slickcop shop either, but an earnest, elected Sheriff and his aging Undersheriff,William C. Gastner. Pushing sixty, and the girth of his Sam Browne uniformbelt, widower Bill has no other life than in law enforcement-and doesn't wantone, even if he's being nudged gently towards retirement. Then big time troublestrikes. A car full of teens out by the lake, running from a stop by Deputy Torrez, goesairborne into a rocky outcrop, killing all five kids and revealing a packageunder the seat. A stash of cocaine this size argues someone-or ones-has broughtbig time crime to the county. Were the dead kids merely innocent dupes?Partying that July Fourth night? Dealing? Searching for answers, Bill deploys his department while dealing with grievingparents, one of whom starts packing a gun. Then a second explosion of violencefells an undercover cop whose fate is decided in a tension-filled, brilliantlydescribed, air ambulance flight. Under pressure, the sheriff's department shows its mettle and pulls together tomake a formidable team. Its weak spot may be Bill whose mind is too tough tocrumble but whose body, long mistreated, gradually succumbs to stress. Ignoringall advice-and sense-he pilots the case to a final dramatic, midairconfrontation where the fate of the killer-and the cop-will be decided....